Pomegranate chitinase III: Identification of a new allergen and analysis of sensitization patterns to chitinases. (November 2018) - Tuppo, Lisa; Giangrieco, Ivana; Alessandri, Claudia; Ricciardi, Teresa; Rafaiani, Chiara; Ciancamerla, Michela; Ferrara, Rosetta; Zennaro, Danila; Bernardi, Maria Livia; Tamburrini, Maurizio; Mari, Adriano; Ciardiello, Maria Antonietta
Graphical abstract: Highlights: Pomegranate class III chitinase is a newly identified allergen. It is a 29 kDa major protein component of pomegranate pulp. Pomegranate class III chitinase is now available for allergy diagnosis. 35% of patients sensitized to chitinase III are positive to kiwifruit chitinase IV. Chitinase III and IV might have a still underestimated role in allergic sensitization. Abstract: Allergy to pomegranate is often associated with severe symptoms. Two allergens have previously been described: 9k-LTP Pun g 1 and pommaclein Pun g 7. This study describes the isolation of a chitinase III, identified by direct protein sequencing and mass spectrometry. It is a 29-kDa protein showing 69% sequence identity with the latex hevamine and IgE binding in dot blotting, immunoblotting and FABER ® test. Chitinase-specific IgE were detected in 69 of 357 patients sensitized to one or more pomegranate allergenic preparations present on the FABER ® test. Using this test, 19.2% of the patients sensitized to kiwifruit chitinase IV were also sensitized to pomegranate chitinase III, rather than to latex chitinase I (7.2%) with which it shares the N-terminal hevein-like domain. In conclusion, a new allergen has been identified, contributing to improving food allergy diagnosis. This study reveals the important role of chitinases III and IV as allergy sensitizers and prompts further investigations.